POTRET KETEGANGAN INTERNAL SINODE NON MAINSTREAM STUDI KASUS GEREJA AM GPR MANADO DITINJAU DARI SOSIOLOGI ORGANISASI - Zaenal Abidin Eko Putro (Harmoni, 2016)
The Ministry of Religious Affairs through its Directorat General for Christianity Affairs has facilitated the establishment of new union’s synod. It is the response of the proposal of legalization that has been proposed for establishing new synod by a number of small group of churches. Some new synods are able to accept the policy and collaborate with other new synods to establish a union of synod. One of the examples is Sinode Am GPR located in Manado city and the surrounding area. However, after being legalized by the government, the synod is overwhelmed by internal conflict. As a result, the management of the synod did not work well. To look at internal structure of this synod, this study adopts organizational sociology theory form Max Weber. It is to see to what extent organizational culture as well as organizational structure works in the synod. This study aims at describing how the government has facilitated the establishment of new synod, board of new synod. But it did not show good performance. Besides, internal conflict occurred among the boards. This paper is based on the qualitative research through in-depth interview, literature study and observation.